Один стих – целая философия (о стихотворении «Całe życie przed tobą…» Станислава Бараньчака) - Гемза, Лех; Gemza, Leсh (Східноєвропейський національний університет імені Лесі Українки, 2014)
В статье представлено образное богатство стихотворения польского писателя Станислава Бараньчака «Całe życie przed tobą…», определена его связь с другими поэтическими произведениями. /The graphic riches of the poem of polish writer Stanislaw Baranchak «Całe życie przed tobą…» (“The whole life is in front of you…”) is represented in the article. It is determined its connection with another poetic works of epoch. The author marked the basic features of “New Wave” poetry, the main attention is payed to its humane motives. In accordance with them, the life becomes the main problem. The waiting hall, in the poem, changes from routine into philosophical space, showing existence category. A human face is characterized in this cut. Stanislaw Baranchak teaches the people to be more attentive to the world, to find the life philosophy in simple things and to appreciate its riches. The poetry doesn’t just depict, but calls and teaches, changing the world to better – it’s the main idea of publication, based on the analysis of Stanislaw Baranchak’s poem – “The whole life is in front of you…”
One Poem – the Whole Philosophy (About the Poem of Stanislaw Baranchak “Całe życie przed tobą…”)
Гемза Л. Один стих – целая философия (о стихотворении «Całe życie przed tobą…» Станислава Бараньчака) / Лех Гемза // Науковий вісник Східноєвропейського національного університету. Сер. «Філологічні науки. Літературознавство». – 2014. – № 9 (286). – С. 19-22.
Keywords: философмя; разговор; гуманизм; «Новая Волна»; новые задания; ситуативность; philosophy; conversation; humanism; “New Wave”; new tasks; situation